Determinan Kinerja Sistem Informasi: Persepsi Pengguna Software Akuntansi - Ika Kristianti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
The purpose of this research is to examine the influence of the quality of the information system of the quality of service on the MYOB application, to test the influence of the quality of the information system on performance of system applications MYOB, and to test the quality of the services against kinerja sistem on applications MYOB. The object of this research i.e. MYOB software. Sample collection using a purposive sampling. Data acquisition as much as 219 respondents. Data processing using Structural Equation models. The results of this research show that the quality of system information significantly negative effect on quality of service, the quality of the system of information and quality of service on performance the system shows no results significantly.